The specific interfacial area in external-circulation-loop airlifts and a bubble column-II. Carboxymethyl cellulose/sulphite solution - Popović, Milan; Robinson, Campbell W. (Chemical engineering science, 1987)
Specific gas-liquid interfacial areas and gas hold-ups in the riser and downcomer sections as well as the liquid circulating velocity were studied using highly viscous pseudo-plastic solutions of carboxymethyl cellulose (CMC). The specific interfacial area was measured by the chemical reaction method (sulphite oxidation). The measurements were carried out in two sizes of external-circulation-loop airlift (ECL-AL) having downcomer-to-riser cross-sectional area ratios ( A d/ A r) of 0.111 and 0.444. Parallel studies in a bubble-column-type fermentor ( A d/ A r = 0) were performed for comparison. All the parameters studied are greatly affected by A d/ A r and the gas superficial velocity, u GR, while the influence of the effective viscosity, η eff, varies from parameter to parameter. A correlation for the specific interfacial area considering the effect of u GR, A d/ A r and η eff is proposed.